Asking about the future: methodological insights from energy biographies. Issue 4 (3rd July 2016) - Shirani, Fiona; Parkhill, Karen; Butler, Catherine; Groves, Chris; Pidgeon, Nick; Henwood, Karen
Abstract : Temporality is fundamental to qualitative longitudinal (QLL) research, inherent in the design of returning to participants over time, often to explore moments of change. Previous research has indicated that talking about the future can be difficult, yet there has been insufficient discussion of methodological developments to address these challenges. This paper presents insights from the Energy Biographies project, which has taken a QLL and multimodal approach to investigating how everyday energy use can be understood in relation to biographical pasts and imagined futures. In particular, we detail innovative techniques developed within the project (e.g. SMS photograph activities) to elicit data on anticipated futures, in ways that engender thinking about participants' own biographical futures and wider societal changes. We conclude by considering some of the significant benefits and challenges such techniques present. These methodological insights have a wider relevance beyond the substantive topic for those interested in eliciting data about futures in qualitative research.